Differential Contribution of the Parental Genomes to a S. cerevisiae × S. uvarum Hybrid, Inferred by Phenomic, Genomic, and Transcriptomic Analyses, at Different Industrial Stress Conditions - Lairón-Peris, María; Pérez-Través, Laura; Muñiz-Calvo, Sara; Guillamón, José Manuel; Heras, José María; Barrio, Eladio; Querol, Amparo (Frontiers in Bioengineering and Biotechnology, 2020)
In European regions of cold climate, S. uvarum can replace S. cerevisiae in wine fermentations performed at low temperatures. S. uvarum is a cryotolerant yeast that produces more glycerol, less acetic acid and exhibits a better aroma profile. However, this species exhibits a poor ethanol tolerance compared with S. cerevisiae. In the present study, we obtained by rare mating, a non-GMO strategy, an interspecific S. cerevisiae x S. uvarum hybrid that improves or maintains a combination of parental traits of interest for the wine industry, such as good fermentation performance, increased ethanol tolerance, and high glycerol and aroma productions.Genomic sequencing analysis showed that the artificial hybrid is an allotriploid, which is very common among natural hybrids. The hybrid genome contains one genome copy from the S. uvarum parental genome and two heterozygous copies of the S. cerevisiae parental genome, with the exception of a monosomic S. cerevisiae chromosome III, where the sex-determining MAT locus is located. This genome constitution supports that the hybrid was likely originated by a rare-mating event between a mating-competent S. cerevisiae diploid cell, hemizygous for the MAT locus, and a haploid S. uvarum spore, although other hypotheses cannot be totally discarded.Moreover, a comparative transcriptomic analysis reveals that each hybrid subgenome is regulating different processes during the fermentation, in which each parental species has demonstrated to be more efficient. Therefore, interactions between the two subgenomes in the hybrid improve those differential species-specific adaptations to the wine fermentation environments, already present in the parental species.